1999
DOI: 10.1111/j.2042-3306.1999.tb03791.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in second‐intention wound healing between horses and ponies: macroscopic aspects

Abstract: Summary Second‐intention healing of deep wounds was studied in 5 horses and 5 ponies. Standardised wounds were created on the distal limbs and hind quarters. Wounds on the metatarsi extended onto the metatarsal bone; the depth of the wounds in the femoral biceps muscle was 18 mm. The wound margins were marked by tattoos. Photographs were taken at weekly intervals to determine the wound area. The relative contribution of contraction and epithelialisation to wound closure was quantified by means of the tattoos. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
126
2
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(141 citation statements)
references
References 11 publications
10
126
2
3
Order By: Relevance
“…19,20,24,37,44 This pitfall has recently been highlighted, since differences in healing vary greatly even between genetically close species. 9,53,79,80 As an example, it has been shown that healing starts earlier and proceeds faster in laboratory animals than in humans, 37 but quite surprisingly, differences in wound healing have even been found between horses and ponies. 79,80 Different animal species have been used as models of wound healing in humans, and some of the data can be adopted as a reference for the age determination of wounds involving the same species.…”
Section: Estimating the Timing Of Lesions Due To Blunt Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…19,20,24,37,44 This pitfall has recently been highlighted, since differences in healing vary greatly even between genetically close species. 9,53,79,80 As an example, it has been shown that healing starts earlier and proceeds faster in laboratory animals than in humans, 37 but quite surprisingly, differences in wound healing have even been found between horses and ponies. 79,80 Different animal species have been used as models of wound healing in humans, and some of the data can be adopted as a reference for the age determination of wounds involving the same species.…”
Section: Estimating the Timing Of Lesions Due To Blunt Traumamentioning
confidence: 99%
“…9,53,79,80 As an example, it has been shown that healing starts earlier and proceeds faster in laboratory animals than in humans, 37 but quite surprisingly, differences in wound healing have even been found between horses and ponies. 79,80 Different animal species have been used as models of wound healing in humans, and some of the data can be adopted as a reference for the age determination of wounds involving the same species. Nonetheless, the lack of precise data that can be used to support the conclusions is a professional challenge for the veterinary forensic pathologist who faces criminal cases in which the interpretation needs to be made ''beyond any reasonable doubt'' rather than ''on the balance of probabilities.''…”
Section: Estimating the Timing Of Lesions Due To Blunt Traumamentioning
confidence: 99%
“…Os equinos apresentam complicações na cicatrização de feridas em regiões distais de membros, quando comparadas às feridas de tronco, e isso se deve a uma longa fase reparatória, caracterizada por grande retração da ferida, baixas taxas de epitelização e cessação precoce da contração da ferida (JACOBS et al, 1984;WILMINK et al, 1999). Os equinos possuem precursores dermais e subcutâneos próprios que predispõem a formação de tecido de granulação exuberante (CHVAPIL et al, 1979), atrasando a cicatrização por inibição da contração da ferida e subsequente epitelização, podendo resultar em grandes áreas ulceradas (JACOBS et al, 1984).…”
Section: Introductionunclassified
“…Im Gewebe führen hypoxische Zustände schließlich zum generalisierten Zelltod. Selbst wenn es zu einer Reperfusion kommen sollte, bilden sich reaktive Sauerstoffradikale, die in Verbindung mit der ischämisch bedingten Energieunterversorgung der Zelle zu einer Reperfusionsnekrose in den betroffenen Körperabschnitten führen (Mosier 2009 Epithelisierung beträgt an der Gliedmaße nur 0,09 mm/Tag, am Rumpf dagegen 0,2 mm/Tag (Theoret 2008b (Wilmink et al 1999a(Wilmink et al und 1999b. Sie bilden mehr Myofibroblasten und zeigen daher eine wesentlich ausgeprägtere Wundkontraktion (Wilmink und van Weeren 2005).…”
Section: Introductionunclassified
“…Sie bilden mehr Myofibroblasten und zeigen daher eine wesentlich ausgeprägtere Wundkontraktion (Wilmink und van Weeren 2005). Die Wundheilung läuft bei ihnen schneller ab, und es treten wesentlich seltener Wundheilungsstörungen auf (Wilmink et al 1999a, Wilmink et al 2002 …”
Section: Introductionunclassified